PELATIHAN MANAJEMEN DAN TATA KELOLA USAHA KOPERASI BINAAN DINAS KOPERASI, UKM, PERINDUSTRIAN PERDAGANGAN KABUPATEN BANYUASIN: - Supriyanto, Agustinus; Noprian, Noprian; Kurniawan, Anton; Twenty Agustine, Grace; Ita, Ita (Jurnal Abdimas Musi Charitas, 2022)
The training is carried out as a community service activity to provide understanding, roles and functions of management and supervisors in making cooperative business operational policies. Some cooperatives still have not held annual member meetings because they do not understand and do not know their duties and responsibilities. The growth of cooperatives in Banyuasin district is quite significant and there needs to be technical assistance for policy making. The training provided is in the form of providing insight and knowledge of cooperatives in accordance with Law no. 25 of 1992. Understanding of strategies related to making a clear work program and preparing financial reports that need to be presented every month as material for management meetings.